Analisis Kepuasan Pasien Rawat Jalan Instalasi Farmasi di Rsud Islamic Centre Kota Agung Tanggamus Dengan Menggunakan Metode Servqual Periode - Ratnasari, Gina; Nopiyansyah, Nopiyansyah; Samsuar, Samsuar; Erniyati, Erniyati; Herdiansah, Riko (JFL : Jurnal Farmasi Lampung, 2023)
Based on the results of the study, it was found that the characteristics of female respondents were more than that of men. Based on the age of the respondents 17-65 years, the results obtained from the analysis were more than 26-35 years old, totaling 32 respondents with a percentage of 41%. Characteristics of respondents based on private employment, self-employed, civil servants, and others were obtained with the largest number, namely other jobs with a value of 54 respondents and a percentage of 69%, characteristics based on education at the level of SD, SMP, SMA, Diploma, Bachelor and others. more respondents with high school level education, amounting to 39 with a percentage of 50%. Based on the sociodemographic data of BPJS respondents and in general, there were more BPJS patients, namely 56 respondents with a percentage of 71%. Based on the results of the analysis of the reality value and the expected value of the five dimensions of servqual reliability, responsiveness, assurance, empathy and physical facilities, the average value or overall real value is 389 and the average expectation value is 391.4. The value of the service quality of the respondents from the five dimensions of servqual, namely reliability, responsiveness, assurance, empathy and physical facilities obtained an average value (-1.6), the value of the level of patient satisfaction based on the five servqual dimensions the average number was obtained (0.994), and Based on the analysis of the level of patient satisfaction with the pharmacy installation service at the Islamic Center Hospital, Kotaagung Tanggamus, the reality value is obtained from the five servqual dimensions with an average value of 389. Keywords: Respondent Satisfaction, RSUD Kotaagung Tanggamus Islamic Centre, Servqual Dimension, Service Quality, Sociodemographics of Respondents.